Tuberculous arthritis: an overview - Hamijoyo, Laniyati (Indonesian Rheumatology Association, 2010)
Tuberculous arthritis is a part of tuberculosis infection. Although the number of this disease is very small compared to the other causes of muskuloskeletal infection, it can cause joint damage and eventually disability to the patient. Tuberculous arthritis should always be considered as one of the differential diagnosis in cases with insidiously developed monoarticulararthritis of the large weight-bearing joints, especially in developing countries where there is a high prevalence of tuberculosis. Early recognition and treatment with antituberculosis drugs provide better outcome for the patient; however, surgery due to unresponsiveness to medical treatment or presence of large abscess,arthroplasty, and arthrodesis may be necessary.